El desafío cultural de la filosofía. Apuntes sobre el actor social en la recepción de la fenomenología en México - Ángel Xolocotzi Yáñez (Nuevo mundo - Mundos Nuevos, 2009)
The fact that philosophy has become a problem for itself in the contemporary scene has also led to a rethinking of its relation with society.  Against the traditional scheme that places the philosopher in social isolation, the author emphasizes some central aspects that lead one to think of the philosopher as a social actor.  For this it is necessary to seek support in radical proposals that break with metaphysical schemes and at the same time open perspectives to think of the inter-subjective character of philosophizing. The phenomenology of Edmund Husserl characterizes itself by such radicalism from the thematic of the very ends of philosophizing. This way opens the possibility to understand the social role of philosophy from its responsibility in cultural transformation.  The appropriation of this perspective is exemplified by the work of the Hiperión Group in Mexico, since it was from their reception of phenomenology and existentialism that allowed them to project philosophy into the sphere of Mexican culture in the mid-20th century.